Challenges in managing change toward total quality management - Abdul Majid, Abdul Halim (UUM College of Business, 2000)
The link and interface between Total Quality Management (TQM) and managing change lay on the ground that TQM is one of the mechanisms for organisational change. Many organisations in both private and public sectors have plunged into implementing TQM that was expected to llead to improved overall performance, but for most, results have been mixed at best. Therefore, this paper discusses the organisational changes that will take place in adopting TQM, how the changes are to be managed and the complexities faced by the organisation in accepting the changes, in terms of organisational structure, system, concepts, behaviour, politics and culture. The structure in which organisational issues are classified into three dimensions or levels-conceptual, system and procedural-derived from the work of Date and Cooper (1993) will be applied throughout this paper as the main basis of discussion.